(untitled) (Andamios, Revista de Investigación Social, 2013)
This essay analyzes the consequences of political anthropomorphism in Plato’s Republic. On the basis of the metaphor that likens the city to a human body, Plato explains how the city must be organized and political justice must be done. I try to explain how the relations between medical and political thought in the Republic bring into play a series of metaphors that create an image of a vertical, ordered, hierarchical State; that is to say, an anti-democratic State. Therefore, this work examines the discursive consequences of Plato’s metaphor, for example: politics conceived as emphasizing the concept of identity by sacrificing differences.